Small things matter: Implications of APP intracellular domain AICD nuclear signaling in the progression and pathogenesis of Alzheimer's disease. (September 2017) - Bukhari, Hassan; Glotzbach, Annika; Kolbe, Katharina; Leonhardt, Gregor; Loosse, Christina; Müller, Thorsten
Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease with tens of millions of people affected worldwide. The pathogenesis is still poorly understood and various therapeutical approaches targeting the amyloid β (Aβ) peptide, a product of the amyloidogenic cleavage of the amyloid precursor protein (APP), failed. Moreover, a couple of studies critically questioned the relevance of Aβ in the pathogenesis of AD. Thus, new ideas need to be studied and one highly interesting hypothesis is the APP mediated signal transduction to the nucleus. As a consequence nuclear –potentially toxic- structures emerge, which were recently found to a high extent in human AD tissue and thus, may contribute to neurodegeneration. Relevant for the signaling machinery are modifications at the very C-terminal end of the precursor protein, the APP intracellular domain (AICD). In this review we update the knowledge on mechanisms on AICD referring to our 2008 article: The amyloid precursor protein intracellular domain (AICD) as modulator of gene expression, apoptosis, and cytoskeletal dynamics—Relevance for Alzheimer's disease (T. Muller, et al., 2008). We summarize how AICD is generated and degraded, we describe its intramolecular motifs, translational modifications, and how those as well as APP dimerization influence AICD generation and function. Moreover, we resume the AICD interactome and elucidate AICDs involvement in nuclear signaling, transcriptional regulation, cell death, DNA repair and cell cycle re-entry and we give insights in its physiological function. Results are summarized in the comprehensive poster "The world of AICD".